In vivo pig models of venous thrombosis mimicking human disease - Kang, Chantal; Bonneau, Michel; Brouland, Jean-Philippe; dit Sollier, Claire Bal; Drouet, Ludovic (Thrombosis and Haemostasis, 2003)
Most animal models of venous thrombosis involve acute thrombosis with hypercoagulability in small rodents. To better replicate human disease, we developed two models in the pig, a species similar to humans in size and in vascular and coagulation reactivity. One model involves de-endothelialisation with 50% or 80% stenosis and the other replacement of a venous segment by a Gore-Tex™ vascular prosthesis. Both models were tested with and without acute induced hypercoagulability (thromboplastin infusion). Thrombi obtained without thromboplastin infusion were composed of a multilayered platelet and a fibrin meshwork structure similar to that usually found in humans. With thromboplastin infusion, the thrombi were homogeneous fibrin structures imprisoning red blood cells. The high incidence of thrombosis obtained with the 80% stenosis model would be useful for studying anticoagulant treatments, whereas the low incidence with 50% stenosis would be useful for evaluating procoagulant effects of conditions or treatments. These new models shed further light on the development of venous thrombi under conditions similar to those seen in humans and may prove useful for investigating anticoagulant and procoagulant effects.
Keywords: Animal models; deep venous thrombosis; pig; thrombus structure